Landscapes of Investigation, Dialogue, and Inclusion: About the Encounter among Deaf and Hearing Students in Mathematics Classes - Moura, Amanda Queiroz [UNESP]; Penteado, Miriam Godoy [UNESP] (Universidad Pedagogica Nacional, 2023)
In this article, we present reflections on the meeting between deaf students and listeners in mathematics classes. In order to contribute to a better understanding of practices based on the concept of inclusion and equity, we bring a discussion about interactions in mathematics classes based on an approach in which the dialogic communication was privileged. Our reference for such discussions is the result of a research that is focused on interaction in which students speak different languages — Portuguese and Brazilian Sign Language. First, we present the context in which the research was carried out. Then, some relevant aspects of the dialogic perspective are elucidated. To illustrate how the interactions took place, we present an episode in which appears interactions among the participants. Finally, we present our reflections on the proposed landscapes of investigation and dialogue in a teaching environment that focuses on inclusion and equity. The results indicate the viability of dialogic interaction between two culturally different groups — deaf and hearing — and their participation in conditions of equity and cooperation during the mathematical learning process. We understand that the reflections and conclusions presented in this paper support mathematics education practices with a focus on diversity.
Paisajes de investigación, diálogo e inclusión: sobre el encuentro entre estudiantes sordos y oyentes en las clases de matemáticas
Keywords: cooperation and equity; critical mathematics education; deaf education; mathematics education and inclusion; meeting amongst the different